Multiple Sclerosis in Saudi Arabia: A literature Review - Omar Mohammed Al-Saeed; Maha Fayez Albogami; Mohamed Hatem (Saudi Journal for Health Sciences, 2021)
Recent reports found that the prevalence of multiple sclerosis (MS) in Saudi Arabia shows an increasing pattern but still less than that recorded in the West. The article will discuss the prevalence, pathology, risk factors, diagnostic modalities, and treatment of MS in Saudi Arabia. In this review, we searched PubMed/Medline database, and all studies that reported the prevalence, pathological and clinical types, diagnostic criteria, diagnostic modalities, and methods of treatment of MS in Saudi Arabia were included. the risk factors included consanguinity, Vitamin D deficiency, viral infection, and change in lifestyle. The presentation is similar to that recorded in western reports, but the course is different. KSA neurologists use the McDonald 2010 criteria for diagnosing MS. In the Kingdom, treatment of MS involves several disease-modifying drugs and these drugs are given according to the clinical course and form of the disease.